Asian Equity Markets : Growth, Opportunities, and Challenges - Kramer, Charles (IMF Working Papers; Working Paper, 2006)
Asian equity markets have grown significantly in size since the early 1990s, driven by strong international investor inflows, growing regional financial integration, capital account liberalization, and structural improvements to markets. The development of equity markets provides a more diversified set of channels for financial intermediation to support growth, thus bolstering medium-term financial stability. At the same time, as highlighted by the May-June 2006 market corrections, the increasing role of stock markets potentially changes the nature of macroeconomic and financial stability risks, as well as the policy requirements for dealing with these risks.